Public transport equity with the concept of time-dependent accessibility using Geostatistics methods, Lorenz curves, and Gini coefficients. (March 2023) - Raza, Asif; Zhong, Ming; Akuh, Raymond; Safdar, Muhammad
Highlights: Study on dynamic multimodal spatial accessibility during specific times of the day. Public transport accessibility to home-based work (HBW) activities is high during off-peak times. Urban areas have equal public transport access to jobs at all peak hours. Transport policies should aim at the fair distribution of public transport infrastructure. Abstract: The primary objective of transport policies is to improve accessibility and mitigate the adverse consequences of private vehicles. Improved accessibility can considerably contribute to urban sustainability and quality of life. To improve accessibility, measuring it as precisely as possible is very important. A greater knowledge of the accessibility levels of public transport systems would not only help in enhancing the level of service but will also aid in resource planning and budgeting (capital costs, operations & maintenance costs, etc.). The research on various accessibility methods used to investigate transportation equity, particularly public transport, revealed that most of these approaches used time-based approaches to analyze public transport accessibility under theoretical traffic conditions and accessibility to public transport corridors, but ignored the overall performance of the transportation network. In this study, we developed an accessibility measurement framework for public transport to capture the performance of the entire transport network in a multimodal fashion and applied the methodology to the City of Wuhan as a case study. The key elements are: (i) develop a multimodal transport network that captures the performance of the entire transport network at a different time of the day. (ii) adopt the utility-based accessibility method to analyze public transport accessibility to opportunities based on the attractiveness of the destination, and (iii) determine the level of the disparity of accessing job opportunities by public transport between the urban and rural areas of the city using Geostatistics methods such as Lorenz curve and Gini Coefficients. The framework adopted in this study allowed us to examine the public transport equity in the study area, and help identify the influencing factors towards enhancing transport policies that consider the fair distribution of public transport infrastructure.